(3JMaI GdYQhS hfRgI GdfahSs - (3GdJLGfj , eMeO Hf CMeO Hf eMeO, CHh YHO Gddg,J (B711 (3g` s ((3eMeO Hf eMeO GdYehQi GdeGdci s)
(3ChdgG (B:s
(3CeG HYO (B:(3aEf Gddg JYGdi Ndb GdEfSGf eLHhdG Ydi GdGaJbGQ , hWHYg ai CUd NdbJg Ydi GdGMJjGL Edi GdScf hGdGVWQGQ hdeG cGf GdJdPP HGdfSGA CYXe GddPGJ QCjfG Cf fLeY ef edM CNHGQgf , heSJXQa fhGOQgf hCTYGQgf s
(3BNQgG (B:s
(3abGd (B:(3GSCdhG ef YaGagG abjd dg (B: (3gi CYa GdfGS ,aCQSd EdjgG eGdG LRjdG hbGd (B: (3JSJYjf Hg Ydi LeGdgG hQhfb COHgG s
(3fSNI SGOSIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B324s
(3U (B370 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B147 s
Keywords: (3GdCOHs